A leitura da erotização da infância e da cultura do estupro: denúncia social na obra Sapato de salto, de Lygia Bojunga - Oliveira, Margareth Laska de (2017)
This research aimed to understand rape culture and the resulting eroticization of childhood built by the patriarchal society and represented in children’s literature, here in the novel “Sapato de Salto”, written by brazilian author Lygia Bojunga, and published in 2006. Based on interpretive hypothesis that the media has a great influence on the eroticization and objectification of the child, it sought to understand how the rape culture and the eroticization of hildhood are socially constructed by the media and reiterated in the idealization of femininity and masculinity, a kind of early maturity of childhood was highlighted as a form of justification for sexual violence. Thus, the relevance of this work is demonstrated in the need to discuss and to denounce child sexual abuse. It hould give voice to those who do not have speech space in the society and are vulnerable within a culture that naturalizes the eroticization of their bodies and blames the victims of pedophilia and child prostitution. For this purpose, feminist theories were used as a basis for discussing gender issues present in the novel, in addition, there was a necessity to construct a theoretical framework that deals with the relations between the novel and a technological environment that validates the female body as a sexual object. Therefore, it was used exploratory research and bibliographical survey about the subject, made it possible to deepen the proposed theme, carrying out a qualitative analysis. It was verified that the high heel shoe, used by the character aunt Inês and later by the character Sabrina, as prostitute, denotes the attempt of early maturity to justify the child prostitution. Thus, it sought to understand how the author builds the symbology of the shoe in contrast to the bare feet and how the consumer society emphasizes this object, influencing through the media the eroticization of childhood, in a need to highlight a discourse that transforms girls early into sexual objects. In addition, it was also verified how the representation of the shoe in the novel refers to the fairy tale of Cinderella, in a intertextual way. This tale is recreated inexhaustibly by the literature and by many other medias. Thus, this research contributes to the discussion and understanding of rape culture and the eroticization of childhood present in the patriarchal society, emphasizing the necessity for reflection about the theme and the pursuit for the protection of childhood and the end of the impunity of sexual aggressors and even more, literature has been stood out as a representation of this society that naturalizes sexual violence.